Intention and Interpretation: A Short History - Grüttemeier, Ralf (De Gruyter, 2022)
Should we take the author's intention into account when interpreting literature? The question has been a subject of fierce debate since the 1940s that shows no signs of abating. The notion of authorial intent, however, has a historical depth that is often overlooked in this debate. This book provides this missing history of authorial intent from Classical Greece to the present day.